Comparison of management and outcomes of ST-segment elevation myocardial infarction patients in Estonia, Hungary, Norway and Sweden according to national ongoing registries. (25th November 2020) - Bloendal, M; Ainla, T; Andreka, P; Edfors, R; Halvorsen, S; Jernberg, T; Jortveit, J; Marandi, T; Janosi, A
Abstract: Background: There is a high need for real-world international comparisons of management of patients with acute myocardial infarction. In Europe Estonia, Hungary, Norway and Sweden are among the few countries with national ongoing acute myocardial infarction registries with a high degree of completeness of data. Purpose: To compare the management and outcome of hospitalized ST-segment elevation myocardial infarction (STEMI) patients in four European countries with a national ongoing myocardial infarction registry. Methods: We compared patient baseline characteristics, use of in-hospital procedures and medications at discharge as well as 30-day and 1-year mortality for all patients admitted with STEMI during 2014–2017 using EMIR (Estonia; n=4, 584), HUMIR (Hungary; n=23, 685), NOMIR (Norway; n=12, 414; data available for years 2013–2016) and SWEDEHEART (Sweden; n=23, 342). Country-level results were compared as aggregated data. Results: Mean age ranged from 65 to 69 years (table 1). Estonia and Hungary had compared to Norway and Sweden a higher proportion of women (resp. 39%; 38% vs. 29%; 31%), as well as patients with hypertension (resp. 79%; 72% vs. 39%; 50%), diabetes (resp. 21%; 27% vs. 14%; 19%) and peripheral artery disease (resp. 9% vs. 6%; 4%). Proportion of current smokers was highest in Norway (38%) and lowest in Sweden (27%). Rates of discharge medications were generally high. The results for in-hospital procedures and mortality are shown in table 1. Estonia had the lowest rates of dual antiplatelet treatment (78%) and statins (86%). Norway had the lowest rates of beta-blockers (80%) and angiotensin converting enzyme inhibitors/ angiotensin II receptor blockers (61%). Conclusions: This cross-country comparison of four national European registries provide new insights into differences in risk factors, treatment regiments and outcomes of patients with STEMI. There are several possible reasons for the observed differences, including differences in underlying expected mortality in the populations, inclusion-criteria and coverage of the registries and variable definitions, that need to be further explored. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Estonian Research Council